Evaluation of tracheal diameter and angles in fetuses with double aortic arch using prenatal ultrasound: implications for postnatal management - Jiang, Caihong; Ling, Wen; Peng, Longzhuang; Guo, Shan; Wu, Qiumei; Chen, Chunxia; Chen, Fa; Li, He; Weng, Zongjie (Frontiers in Medicine, 2024)
Objective: This study aims to analyze the value of prenatal ultrasound in the screening, diagnosis, and treatment of double aortic arch (DAA) malformations.A retrospective analysis was conducted on 31 fetal cases with double aortic arch anomalies over a 12-year period from June 1, 2011 to June 1, 2023. The assessment included combined measurements of fetal tracheal internal diameter Z-score and DAA pinch angle, along with ultrasonographic findings, associated anomalies, genetic abnormalities, postnatal CTA images, and long-term postnatal outcomes.Results: Of the 31 fetal double aortic arch cases, 15 were right aortic arch dominant, 2 were left aortic arch dominant, and 14 had a balanced double arch. Genetic testing was performed on 19 cases, revealing abnormalities in 2 cases, including one Turner syndrome, and one carrier of ichthyosis gene with heterozygous deletion. Out of the total cases, 29 were delivered, and 2 cases were terminated. Prenatal diagnosis accurately identified 29 cases (29/31, 93.5%), which was confirmed by postnatal pathological anatomy, echocardiography, surgery or CTA. Fetal tracheal internal diameter Z-scores were significantly smaller in the symptomatic group than in the asymptomatic group (-1.27±0.49 vs -0.68±0.60, P=0.018). The area under the curve was 0.776 (95% confidence interval, 0.593-0.960) using a tracheal internal diameter z-score cutoff of -0.73 with a sensitivity of 90% and specificity of 64.7%. The double arch pinch angle was significantly smaller in the symptomatic group than in the asymptomatic group [52.50° (38.25° to 59.00°) vs 60.00° (53.50° to 70.50°), P=0.035]. The area under the curve was 0.744 (95% confidence interval, 0.554-0.935), and the sensitivity for determining the presence or absence of symptoms was 90% when the cutoff value was 62.5°, with a specificity of 47.1%. Fifteen cases opted for surgery with favorable surgical outcome.Prenatal echocardiography demonstrates good diagnostic efficacy for fetal double aortic arch. It is also essential to detect the presence of other underlying intra-and extracardiac malformations and genetic abnormalities. There is a significant difference in prenatal tracheal internal diameter Zscores and double arch pinch angle between asymptomatic and symptomatic DAA infants. Symptomatic infants require early surgery, while asymptomatic infants should be monitored.